Biomechanics of the head for Olympic boxer punches to the face - Walilko, T. J.; Viano, D. C.; Bir, C. A. (British Journal of Sports Medicine, 2005)
Objective: The biomechanics of the head for punches to the jaw and the risk of head injury from translational and relational acceleration were studied.